A Use Case of Patent Classification Using Deep Learning with Transfer Learning - Henriques, Roberto (2022)
Henriques, R., Ferreira, A., & Castelli, M. (2022). A Use Case of Patent Classification Using Deep Learning with Transfer Learning. Journal of Data and Information Science, 7(3), 49-70. https://doi.org/10.2478/jdis-2022-0015 ----- Funding Information: This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.